Interprofessional LGBT Health Equity Education for Early Learners - Katie F. Leslie; Stacie Steinbock; Ryan Simpson; V. Faye Jones; Susan Sawning (Association of American Medical Colleges, 2017)
Introduction The eQuality project at the University of Louisville aims to train future physicians to deliver equitable quality care for all people by creating an integrated educational model utilizing the competencies identified in the AAMC's Implementing Curricular and Institutional Climate Changes to Improve Health Care for Individuals Who Are LGBT, Gender Nonconforming, or Born With DSD. This foundational interprofessional health equity session for early learners addresses knowledge and attitude milestones relating to interprofessional collaboration, professionalism, and systems-based practice competencies for lesbian, gay, bisexual, and transgender (LGBT) populations. Methods First-year medical students were assigned to interprofessional teams of approximately 10 health sciences students each. Students participated in a 75-minute session utilizing a group case study activity, including a systems lecture exploring social determinants and community resources related to LGBT health. Students collaboratively discussed the case and recorded strategies for optimal patient care. The Readiness for Interprofessional Learning Scale and health disparities attitudes and knowledge scales were administered pre-/postsession. Results One hundred fifty-eight first-year medical students participated in the session. Posttest scores reflected an improvement for all disparities knowledge items (p < .001), and an increased interest in working with other health professions students on future projects (p < .001). Changes in attitudes toward systemic and social factors affecting health were also observed. However, content analysis of worksheets revealed that only 36% of teams identified specific action steps for the case scenarios. Discussion This session was effective in improving knowledge and attitudes related to LGBT health equity and interprofessional education.